콩류 아라비노갈락탄 용액의 유변학적 성질 - 김경이(Kyeong Yee Kim); 김춘영(Choon Young Kim) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2019)
The aim of this study was to investigate the rheological properties of arabinogalactans (AGs) solution isolated from moth bean (MB), navy bean (NB), and soybean (SB) including monosaccharide compositions, intrinsic viscosity, steady shear and dynamic shear rheological properties. The major monosaccharides in MB, NB, and SB were arabinose (64.8, 51.4, and 42.6%) and galactose (13.4, 19.6, and 46.2%). The yield stresses for 5% (w/v) NB and 2.5% (w/v) SB solutions were assessed as 2.10 Pa and 1.98 Pa, respectively, but in case of MB solution, it was observed to be negligible. While 5% MB solution showed rheopectic property, 5% NB and SB solutions showed thixotropic properties. As a result of frequency sweep experiment, the G' values in 2.5% MB and NB were larger than the G'' value showed but 2.5% SB exhibited G'' value greater than G'. These results would be useful for future application as a food additive in the food industry.